Hydration status of rugby league players during home match play throughout the 2008 Super League season - O`Hara, J. P.; Jones, B. L.; Tsakirides, C.; Carroll, S.; Cooke, C. B.; King, R. F. G. J. (Applied Physiology, Nutrition, and Metabolism, 2010)
The hydration status of rugby league players during competitive home match play was assessed throughout the 2008 Super League season. Fourteen players from 2 Super League clubs were monitored (72 observations). On arrival, 2 h prior to kick off, following normal prematch routines, players` body mass were measured following a urine void. Prematch fluid intake, urine output, and osmolality were assessed until kick off, with additional measurements at half time. Fluid intake was also monitored during match play for club B only, and final measurements of variables were made at the end of the match. Mean body mass loss per match was 1.28 ± 0.7 kg (club A, 1.15 kg; club B, 1.40 kg), which would equate to an average level of dehydration of 1.31% (mass loss, assumed to be water loss, expressed as a percentage of body mass), with considerable intra-individual coefficient of variation (CV, 47%). Mean fluid intake for club B was 0.64 ± 0.5 L during match play, while fluid loss was 2.0 ± 0.7 L, with considerable intra-individual CV (51% and 34%, respectively). Mean urine osmolality was 396 ± 252 mosm/kg on arrival, 237 ± 177 mosm/kg prematch, 315 ± 133 mosm/kg at half time, and 489 ± 150 mosm/kg postmatch. Body mass losses were primarily a consequence of body fluid losses not being completely balanced by fluid intake. Furthermore, these data show that there is large inter- and intra-individual variability of hydration across matches, highlighting the need for future assessment of individual relevance.